The anticancer immune response: indispensable for therapeutic success? - Zitvogel, Laurence (American Society for Clinical Investigation, 2008)
Although the impact of tumor immunology on the clinical management of most cancers is still negligible, there is increasing evidence that anticancer immune responses may contribute to the control of cancer after conventional chemotherapy. Thus, radiotherapy and some chemotherapeutic agents, in particular anthracyclines, can induce specific immune responses that result either in immunogenic cancer cell death or in immunostimulatory side effects. This anticancer immune response then helps to eliminate residual cancer cells (those that fail to be killed by chemotherapy) or maintains micrometastases in a stage of dormancy. Based on these premises, in this Review we address the question, How may it be possible to ameliorate conventional therapies by stimulating the anticancer immune response? Moreover, we discuss the rationale of clinical trials to evaluate and eventually increase the contribution of antitumor immune responses to the therapeutic management of neoplasia.